REPONSES TO THE QUESTION OF THE SCHOOLING OF REFUGEES IN THE COMMUNE OF MANDJOU: MODALITIES AND EVALUATION FROM 2013 TO 2023 - Hanse Gilbert MBENG DANG; Nadège Thamar BILOUNGA NTOMBA; Jeannette Lohr ELANGA THOMBA (Universitaria Publishing House, Craiova, 2023)
It's no truism to admit that many Central African refugee children don't go to school in a world where education, a fundamental right, is the basis of all development. Several hundred of these children are victims of under-schooling and other school wastage. When they are enrolled in Cameroonian schools in general, and in the commune of Mandjou in particular, they leave early, despite the enormous resources mobilized by public authorities and development partners. The truth is that MDG goal number 3, "education for all by 2015", has not been achieved. The aim of this study is to take a systemic and critical approach to assessing the various measures and policies relating to the schooling of refugees in the Mandjou commune, in the East Cameroon region, in a context where inclusive education is intended to give the most vulnerable groups greater opportunities for integration. It concludes with a series of recommendations that could help the government and humanitarian organizations. To achieve this, a hypothetico-deductive approach was favored, based on the collection of data from various sources, in particular interviews with resource persons, followed by surveys